2020
DOI: 10.1002/oby.22778
|View full text |Cite
|
Sign up to set email alerts
|

Upper and Lower Extremity Measurement of Tissue Sodium and Fat Content in Patients with Lipedema

Abstract: Objective: The aim of this study is to compare tissue sodium and fat content in the upper and lower extremities of participants with lipedema versus controls using magnetic resonance imaging (MRI). Methods: MRI was performed at 3.0 T in females with lipedema (n = 15, age = 43.2 ± 10.0 years, BMI = 30.3 ± 4.4 kg/m 2 ) and controls without lipedema (n = 14, age = 42.8 ± 13.2 years, BMI = 28.8 ± 4.4 kg/m 2 ). Participants were assessed for pain and disease stage. Sodium MRI was performed in the forearm and calf t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 30 publications
1
31
0
2
Order By: Relevance
“…Standardized 23 Na MRI was used to measure brain TSC, and no difference was found in lipedema. Coupled with prior evidence of elevated TSC in the lower extremities (14), this suggests that altered sodium biodistribution is not systemic. This could be attributed to the absence of adipose tissue in the brain, in contrast to the extremities, where hypertrophic gynoid fat is associated with sodium deposition, potentially due to lymphovenous insufficiency.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Standardized 23 Na MRI was used to measure brain TSC, and no difference was found in lipedema. Coupled with prior evidence of elevated TSC in the lower extremities (14), this suggests that altered sodium biodistribution is not systemic. This could be attributed to the absence of adipose tissue in the brain, in contrast to the extremities, where hypertrophic gynoid fat is associated with sodium deposition, potentially due to lymphovenous insufficiency.…”
Section: Discussionmentioning
confidence: 68%
“…Echocardiography studies have identified cardiac abnormalities, including enlarged mitral annulus, increased left ventricular volume (11), unusual left ventricular rotation (12), and increased aortic stiffness (13). Peripheral tissue sodium content and subcutaneous fat volume were shown to be elevated in the legs of patients with lipedema (14,15), similar to other conditions of circulatory dysfunction that do not directly or exclusively involve the legs (16,17).…”
Section: Introductionmentioning
confidence: 96%
“…Increased fibrosis and changing composition of the ECM is characteristic of and can further drive adipose tissue dysfunction [ 92 , 93 , 94 ]. Fibrotic ECM could also be a source of elevated tissue sodium content in lipedema leg SAT observed on molecular-imaging studies [ 95 , 96 ]. Comparative studies of imaging to histology should be carried out in lipedema and lymphedema to improve our understanding of SAT composition and function in the setting of fibrosis.…”
Section: Molecular Regulators and Pathophysiologymentioning
confidence: 99%
“…In addition, excess tissue Na + signal was identified in the lower limbs of patients with lipedema [ 84 •], a condition characterised by excess accumulation of adipocytes and inflammatory interstitial fluid [ 85 , 86 ], in systemic sclerosis [ 87 ] and systemic lupus erythematosus [ 88 ]. Such evidence links the phenomenon to inflammation in general, without any direct implication on high blood pressure; this is also in keeping with high Na + signal in the brain of patients with multiple sclerosis [ 89 ].…”
Section: Not Only Hypertension!mentioning
confidence: 99%